Improve PGP Cryptography Protocol Using Genetic NTRU Technique - A. Sarab, Sura (Iraqi Journal of Science, 2023)
The strong cryptography employed by PGP (Pretty Good Privacy) is one of the best available today. The PGP protocol is a hybrid cryptosystem that combines some of the best features of both conventional and public-key cryptography. This paper aim to improve PGP protocol by combined between the Random Genetic algorithm, NTRU (N-th degree Truncated polynomial Ring Unit) algorithm with PGP protocol stages in order to increase PGP protocol speed, security, and make it more difficult in front of the counterfeiter. This can be achieved by use the Genetic algorithm that only generates the keys according to the Random Genetic equations. The final keys that obtained from Genetic algorithm were observed to be purely random (according to the randomness tests) and it was used instead of the keys that generated from random movements of mouse in the standard PGP protocol. In addition, the new PGP protocol uses the NTRU technique for encryption process instead of RSA algorithm. NTRU algorithm is secure to most attack methods and performs operations much faster than RSA. So, the New-PGP increased secure condition to the PGP protocol and made it more robust and efficient.